1986
DOI: 10.1021/je00045a032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [2.2]isoindolinophanes and dihydro[c]furanophane and their charge-transfer complexes with .pi.-acceptors

Abstract: Reaction of 4.5.12.13tetraki»(bromomethyl)[2.2]paracyclophane (6) with methane and p -toluenesulfonamide results In formation of dlhydrobenzo[c ]furanophane (4); however the desired Isolndolophane 3 was not formed. Formation of 4 was supported by the Interaction of 4.5.12.13tetrakls(hydroxymethyl)[2.2]paracyclophane (2) with -toluenesuHonic acid. On the other hand, Interaction of 6 with some aromatic amines gave the corresponding [2.2]lsolndollnophane derivatives 8a-f. Charge-transfer complexes of 8a-f (donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The yellow precipitate formed was isolated by filtration. (14), 510 (12), 410 (14), 308 (100), 280 (20), 204 (16), 126 (20), 102 (34), 77 (30).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The yellow precipitate formed was isolated by filtration. (14), 510 (12), 410 (14), 308 (100), 280 (20), 204 (16), 126 (20), 102 (34), 77 (30).…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the reaction of 9 with aniline afforded the corresponding syn-isoindolenophane. 16 Interestingly, we have also investigated the synthesis of the heterophanes 17a,b as a general method for preparing this class of compound, so as to facilitate their future synthesis. Attempts to prepare the heterophanes 17a,b from the reaction of 9 with binucleophilic compounds such as 2-aminophenol and 2-aminothiophenol proceeded, but in very low yields of the desired products.…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations